Criminogenic asymmetries as the trigger of International fraud victimization in Indonesia – China trade relations. Study of victimization of Indonesian exporters - Raden Muhammad Jauhari,; Meliala, Adrianus (Technium Social Sciences Journal, 2021)
This study aims to examine criminogenic asymmetries as the triggering factors for the victimization of international fraud in Indonesia – China trade relations. The research uses a descriptive-qualitative approach with a case study method and limits it only from the perspective of Indonesia as a victim. Based on the identification and interpretation of research data using Levi’s (2009) typology and stages of fraud victimization and the concept of criminogenic asymmetries of Passa (1999), it was found that fraud crimes by transnational organized criminal groups occured on both sides of the Indonesia – China trade relationship, both as perpretrators and as victims. It also found victimization efforts by Chinese organized crime groups against Indonesian exporters when entering into trade contracts. There are four asymmetric criminogenic factors that have an impact on the victimization of Indonesian exporters in trade relations with China, namely the legal system, technology, knowledge and culture. Researchers also found that victimization by Chinese companies against Indonesian exporters is a form of international fraud. The researcher suggests that the victimization by Chinese criminal groups against Indonesian exporters should receive national legal facilities so that losses can be avoided.